Ameloblastoma Or Dentigerous Cyst- A Diagnostic Quandary (Journal of Pharmaceutical Negative Results, 2022)
Orofacial swellings are a major concern these days as they are first interrogated by a pediatric dentist in younger age group. The range of swelling varies from orofacial infections to tumors. Ameloblastoma is rare to be seen in younger age group but still plays an important role in pediatric dentistry. Ameloblastoma is benign and odontogenic and nature most importantly they are recurrent in nature. Unicystic ameloblastoma is majorly confused with keratocyst, due to which it becomes a quandary in diagnosis. It mostly effects mandible and female predilection is higher. In this case report, we present a unicystic ameloblastoma with mural proliferation in 8 years old child.